Prioritising conservation actions for extremely data-poor species: A risk assessment for one of the world's rarest marine fishes. (April 2022) - Bessell, Tyson J.; Stuart-Smith, Jemina; Barrett, Neville S.; Lynch, Tim P.; Edgar, Graham J.; Ling, Scott; Appleyard, Sharon A.; Gowlett-Holmes, Karen; Green, Mark; Hogg, Carolyn J.; Talbot, Simon; Valentine, Joe; et al.
Abstract: Effective prioritisation of research and conservation action for threatened species requires understanding the relative importance of the various pressures they face. This can be difficult for rare, cryptic, and data-deficient species, particularly when drivers of population decline are complex and indirectly impact one another. We developed a risk assessment-based approach that accounts for cascading ecological changes and indirect impacts between human and environmental pressures for threatened species, for application when data-dense assessment approaches are not possible. We applied this framework to the Critically Endangered red handfish ( Thymichthys politus ), one of the rarest and most threatened fishes in the world, currently only known from two highly localised populations in Australia's south-east. Our approach identified the unique life history strategy of handfishes, coastal warming, indirect ecological pressures caused by recreational fishing, urban development, and poaching as the greatest current threats to the persistence of the species. Mitigation options identified to have the greatest immediate reduction in extinction risk include an ex situ captive population and release program to bolster numbers in the wild, and engagement with the commercial sea urchin fishery to help reduce impact within critical habitat. Our risk assessment process may provide a useful framework for allowing managers to make more informed and supported decisions for other species that are similarly data-poor, and when decisions would otherwise necessarily rely on best guesses that do not consider their broader ecological, environmental and anthropogenic contexts. Highlights: We developed a process for identifying and prioritising conservation and research needs for data-poor, threatened species. The approach considers cascading ecological changes and indirect impacts between human and environmental pressures. The process may help managers to make informed and supported decisions for other similarly data-poor species.